Role of Biogenic Amines in Oviposition by the Diamondback Moth, Plutella xylostella L - Li, Fan; Li, Ke; Wu, Li-Juan; Fan, Yong-Liang; Liu, Tong-Xian (Frontiers in Physiology, 2020)
Oviposition is an important reproductive behavior that is triggered by mating in insects, and biogenic amines might be involved in its regulation. The effects of biogenic amines on oviposition have only been studied in a few insect species, and the findings to date have not been conclusive. In addition, there are few studies on the effects of biogenic amines on oviposition of the diamondback moth, Plutella xylostella L. Here, we tested how mating and biogenic amines regulate oviposition of P. xylostella by injecting amines and amine receptor antagonists into virgin and mated females and counting the number of eggs laid afterward. Biogenic amines of octopamine and tyramine could induce virgin adults of P. xylostella to lay eggs, while dopamine and serotonin had no such effect on oviposition. Furthermore, the octopamine antagonists mianserin, epinastine, and phentolamine inhibited oviposition by mated females. The tyramine antagonist yohimbine, dopamine antagonist SCH23390, and serotonin antagonist ketanserin did not block oviposition by mated females, and octopamine and tyramine-inducing oviposition by virgin females could be inhibited by the octopamine antagonists mianserin and epinastine instead of the tyramine antagonist yohimbine. We conclude that octopamine and its receptors are involved in mating-triggered oviposition in P. xylostella, while tyramine acts as a subsidiary. Further, the inducing effect of tyramine on oviposition is achieved via octopamine receptors instead of tyramine receptors. This experiment is helpful to further understand the role of biogenic amines in mating regulation and to provide a new strategy for controlling P. xylostella.